Rasionalisme dan Empirisme: Dua Paradigma Utama dalam Filsafat Pengetahuan - Widad, Shofwah El; Amalia, Farida Nova; Mubarak, Ahmad Hafidz (Maliki Interdisciplinary Journal, 2025)
Rationalism and empiricism are two major paradigms in the philosophy of knowledge, both providing a crucial foundation for the development of modern philosophy. These two schools of thought have shaped the way humans understand the sources, processes, and validity of knowledge from the time of Ancient Greece to the contemporary era. Rationalism provides a primary source of knowledge that is certain, universal, and independent of sensory experience. However, empiricism argues that all knowledge originates from the senses. The debate between these two schools of thought has not only influenced the development of philosophy but also formed the basis for the formation of the modern scientific methodology. In the contemporary context, these two schools of thought are relevant because science requires a balance between conceptual clarity and empirical evidence. Understanding these two schools of thought not only provides a conceptual foundation but also helps formulate a more comprehensive, critical, and accountable approach.